In House Training peningkatan kompetensi guru dalam pelaksanaan pendidikan vokasional di SLB Negeri Rembang - Fajar Widyaningrum, Puput (Literal: Disability Studies Journal, 2023)
The independence of students with special needs in the future is prepared through vocational education. Teacher competency in carrying out vocational education needs to be improved so that the quality of educational services can be better. Through a qualitative approach, this research aims to present an objective picture regarding the implementation of increasing teacher competency in providing vocational education in Rembang State Special Schools. Based on the purposive sampling technique, the informants were eight class teachers who also served as vocational teachers, consisting of three men and five women. Data collection was carried out in November 2023. Data collection was carried out by observation, interviews, and documentation. Data validation uses member check techniques, triangulation techniques, and researcher persistence. Data were analyzed through inductive analysis which consists of data reduction, data display, and concluding.  The results of this research indicate that training is still needed for teachers in special schools to develop vocational education programs for students with special needs involving various approaches.